Fanggui Li Collection - Li, Fanggui; Mandeville, François; Ferrier, Baptiste; Thompson, Laurence C.; Thompson, M. Terry (1928)
The heart of the Fanggui Li Collection is comprised of ten notebooks kept by the Chinese-American linguist Fanggui (Fang-Kuei) Li relating to his research on the Chipewyan [Dene] language in 1928. Recorded in the field, these texts consist of phonetic transcriptions of stories elicited from François Mandeville in Chipewyan (Denesuline); (and, in one instance, Baptiste Ferrier) in July 1928, with interlinear English translations. The topics of these stories include myths, folklore, and tribal history as well as activities like fishing, tanning a moose hide, or making a canoe. The balance of the collection consists of an extensive slipfile for the Chipewyan [Dene] language, and two audio cassettes of oral history interviews conducted by Laurence C. Thompson and M. Terry Thompson in 1982, concerning Li's memories of Edward Sapir and other colleagues in linguistics. Interview topics include Li's early education, experience at the University of Chicago, Leonard Bloomfield, Edward Sapir's influence on his course of study, Li's fieldwork on the Mattole language in Northern California in the late 1920s, discrimination against Chinese in that region at that time, Li's work with Sapir on the Hupa reservation, and various aspects of linguistic methodology of the times, including recording with wax cylinders. See the finding aid for more information, including more details on the contents of each notebook and the two audio cassettes, and for related material.